Trade, Growth, and Poverty : A Selective Survey - Berg, Andrew; Krueger, Anne. (Washington, D.C. : International Monetary Fund, 2003)
This survey of the recent literature asks: how important is trade policy for poverty reduction? We consider the effects of openness on poverty in two components: the effect of openness on average income growth, and the effect on distribution for a given growth rate. Evidence from a variety of sources (cross-country and panel growth regressions, industry and firm-level research, and case studies) supports the view that trade openness contributes greatly to growth. Moreover, trade openness does not have systematic effects on the poor beyond its effect on overall growth. Trade policy is only one of many determinants of growth and poverty reduction. Trade openness has important positive spillovers on other aspects of reform, however, so that the correlation of trade with other pro-reform policies speaks to the advantages of making openness a primary part of the reform package.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet